Ecological stress, amygdala reactivity, and internalizing symptoms in preadolescence: Is parenting a buffer?. (July 2021) - Demidenko, Michael I.; Ip, Ka I.; Kelly, Dominic P.; Constante, Kevin; Goetschius, Leigh G.; Keating, Daniel P.
Abstract: Ecological stress during adolescent development may increase the sensitivity to negative emotional processes that can contribute to the onset and progression of internalizing behaviors during preadolescence. Although a small number of studies have considered the link among the relations between ecological stress, amygdala reactivity, and internalizing symptoms in childhood and adolescence, these studies have largely been small, cross-sectional, and often do not consider unique roles of parenting or sex. In the current study, we evaluated the interrelations between ecological stress, amygdala reactivity, subsequent internalizing symptoms, and the moderating roles of parenting and sex among 9- and 10-year-old preadolescents from the Adolescent Brain Cognitive Development (ABCD) Study ®. A subset of participants who met a priori quality control criteria for bilateral amygdala activation during the EN -back faces versus places contrast ( N  = 7, 385; Mean Age = 120 months, SD  = 7.52; 49.5% Female) were included in the study. A confirmatory factor analysis was performed to create a latent variable of ecological stress, and multiple structural equation models were tested to evaluate the association among baseline ecological stress and internalizing symptoms one year later, the mediating role of amygdala reactivity, and moderating effects of parental acceptance and sex. The results revealed a significant association between ecological stress and subsequent internalizing symptoms, which was greater in males than females. There was no association between amygdala reactivity during the Faces versus Places contrast and ecological stress or subsequent internalizing symptoms, and no mediating role of amygdala or moderating effect of parental acceptance on the association between ecological stress and internalizing symptoms. An alternative mediation model was tested which revealed that there was a small mediating effect of parental acceptance on the association between ecological stress and internalizing symptoms, demonstrating lower internalizing symptoms among preadolescents one year later. Given the lack of association in brain function, ecological stress and internalizing symptoms in preadolescents in this registered report, effects from comparable small studies should be reconsidered in larger samples.